Diseño y construcción de pulidor para preparación de muestras metalográficas para la Universidad Nariño sede Ibagué (2023)
This document includes the technical specifications of the equipment built and the results of the tests performed. The equipment meets the performance of a commercial one, but at a lower cost, which is beneficial for the Antonio Nariño University, Ibagué campus. The importance of proper use of metallographic samples and the need for cooling during the polishing process is also emphasized. This document is useful for students and professionals in metallurgy interested in designing and building equipment efficiently.